Core temperature up to 41.5ºC during the UCI Road Cycling World Championships in the heat - Racinais, S.; Moussay, S.; Nichols, D.; Travers, G.; Belfekih, T.; Schumacher, Y. O.; Periard, J. D. (British Journal of Sports Medicine, 2019)
Objective To characterise the core temperature response and power output profile of elite male and female cyclists during the 2016 UCI Road World Championships. This may contribute to formulating environmental heat stress policies.